O ensino de operações com números racionais em sua representação fracionária: formação continuada de professores - Vernizzi, Mario Alberto Zambrana (2022)
This dissertation presents four didactic sequences, for the teaching of operations with rational numbers in their fractional representation, to be discussed with teachers who work with the initial grades of Elementary School II, considering that through the bibliographic review we found a small number of researches dealing with these operations. In addition, we observed the lack of autonomy of teachers to develop activities of this type, which leads us to the idea of investigating to answer the following question: what knowledge teachers of mathematics mobilize regarding the teaching of operations with rational numbers in their fractional representation during the discussion of a teaching sequence for the sixth year of elementary school? We will focus the operations on the part-whole conception, starting from the representations of flat geometric figures, as it is the most common both in textbooks and in teachers' practice, although the other conceptions may appear during the solutions. We will present a brief description about the Theory of Registers of Semiotic Representation (DUVAL, 2009), as well as about the Theory of Conceptual Fields (VERGNAUD, 1977) for believing that the junction of these theories can help in the teaching of such operations. We suggest further research in the field in order to contribute to Mathematics Education . Keywords: Fractions; Fractional Numbers; Operations; Training